The Effect of Emotional Intelligence on Public Sector Employee’s Affective Commitment - Triyono, Triyono; Tjahjono, Heru Kurnianto (Journal of Governance and Public Policy, 2023)
Commitment is vital in keeping and maintaining integrity within the organization, especially in public organizations. In addition to maintaining integrity, commitment is much needed in organizational change. People with affective commitment who join the organization of their own volition will support the changes made if they feel they are good for the organization. This quantitative study used primary data collected with an online survey facility. The data collection used the non-probability sampling technique of convenience sampling. The sample involved 255 active Directorate General of Customs and Excise employees with work locations across various parts of Indonesia. The data obtained were processed with JASP v 0.16 application with simple regression techniques and Structural Equation Modeling (SEM). The study’s results support the initial hypothesis that emotional intelligence positively affects employees’ affective commitment. In addition, the study’s results support the second hypothesis that public service motivation mediates the effect of emotional intelligence on affective commitment.